John Bristow's Psychological Problems in Robert Galbraith's The Cuckoo's Calling (NOBEL: Journal of Literature and Language Teaching, 2015)
John Bristow is the minor character in the novel The Cuckoo's Calling who has a problem with his decision in satisfying his id and superego. He is an ordinary man who has a job, family and girlfriend. However, his jealousy to his brother and sister forces him to kill them. This study focuses on analyzing the characterization of John Bristow, how his ego manages his id and superego and how anxieties appear as the effects of the problem. The aim of this paper is to examine the motif that leads John kills his step brother and sister. Psychology theory by Sigmund Freud is applied to analyze the character's psychological problem. Perspective from Al-Quran is used to examine the reflection of Qabil's character in the story of Habil and Qabil to John Bristow's.